Corporate Scandals and Household Stock Market Participation - GIANNETTI, MARIASSUNTA; WANG, TRACY YUE (Journal of Finance, 2016)
ABSTRACT We show that, after the revelation of corporate fraud in a state, household stock market participation in that state decreases. Households decrease holdings in fraudulent as well as nonfraudulent firms, even if they do not hold stocks in fraudulent firms. Within a state, households with more lifetime experience of corporate fraud hold less equity. Following the exogenous increase in fraud revelation due to Arthur Andersen's demise, states with more Arthur Andersen clients experience a larger decrease in stock market participation. We provide evidence that the documented effect is likely to reflect a loss of trust in the stock market.